Characterizing Patient-Friendly "Micro-Explanations" of Medical Events - Wilcox, Lauren; Morris, Dan; Tan, Desney; Gatewood, Justin; Horvitz, Eric (CHI '11 Proceedings of the SIGCHI Conference on Human Factors in Computing Systems, 2011)
Patients’ basic understanding of clinical events has been shown to dramatically improve patient care. We propose that the automatic generation of very short microexplanations, suitable for real-time delivery in clinical settings, can transform patient care by giving patients greater awareness of key events in their electronic medical record. We present results of a survey study indicating that it may be possible to automatically generate such explanations by extracting individual sentences from consumer-facing Web pages. We further inform future work by characterizing physician and non-physician responses to a variety of Web-extracted explanations of medical lab tests.